2010
DOI: 10.1094/phyto-100-4-0390
|View full text |Cite
|
Sign up to set email alerts
|

Phloem Cytochemical Modification and Gene Expression Following the Recovery of Apple Plants from Apple Proliferation Disease

Abstract: Recovery of apple trees from apple proliferation was studied by combining ultrastructural, cytochemical, and gene expression analyses to possibly reveal changes linked to recovery-associated resistance. When compared with either healthy or visibly diseased plants, recovered apple trees showed abnormal callose and phloem-protein accumulation in their leaf phloem. Although cytochemical localization detected Ca(2+) ions in the phloem of all the three plant groups, Ca(2+) concentration was remarkably higher in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
54
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 40 publications
7
54
0
Order By: Relevance
“…The molecular mechanisms involved in the interaction between phytoplasmas and host plants are so far largely unknown and only recently some gene expression changes have been identified [2,6,8,10,17]. Using in vitro micro-propagated apple plantlets, we have shown effects on gene expression and biochemical alterations related to phytoplasma infection.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The molecular mechanisms involved in the interaction between phytoplasmas and host plants are so far largely unknown and only recently some gene expression changes have been identified [2,6,8,10,17]. Using in vitro micro-propagated apple plantlets, we have shown effects on gene expression and biochemical alterations related to phytoplasma infection.…”
Section: Discussionmentioning
confidence: 92%
“…Considerable and tissue specific modulations were found for genes related to the cell wall metabolism, which are most likely correlated to the anatomical aberrations found on the plates of sieve tubes in infected plants [2,6,10]. Jagoueix-Eveillard et al [5] reported a down-regulation of a putative sterol-C-methyltransferase in periwinkle after infection with stolbur phytoplasma and associated this gene repression with leaf yellowing and stunting.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Ultrastructural, cytochemical, and gene expression analyses of phloem of healthy, visibly diseased, and recovered apple trees revealed various differences. Recovered trees are characterized by the presence of hydrogen peroxide (H 2 O 2 ), callose and phloem protein accumulation, and the upregulation of genes involved in synthesis of callose and phloem protein (Musetti et al 2004(Musetti et al , 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Abiotic and biotic agents already known to induce systemic acquired resistance have been also hypothesized to be involved in recovery (1,13,44). Recent results obtained by investigating the physiological and genetic bases of recovery (37)(38)(39)(40) supported a strict correlation between recovery and a type of acquired or induced resistance in the host plant. Very recently, it has been shown that AP induced an increase in salicylate in apple plants, followed by a decline accompanied by a subsequent increase of jasmonic acid (JA) during recovery (42).…”
mentioning
confidence: 88%